Centralized Gap Clearance Control for Maglev Based Steel-Plate Conveyance System - Guney, Omer Faruk; Bozkurt, Ahmet Fevzi; Erkan, Kadir (UNIV SUCEAVA, FAC ELECTRICAL ENG, 2017)
The conveyance of steel-plates is one of the potential uses of the magnetic levitation technology in industry. However, the electromagnetic levitation systems inherently show nonlinear feature and are unstable without an active control. Well-known U-shaped or E-shaped electromagnets cannot provide redundant levitation with multiple degrees of freedom. In this paper, to achieve the full redundant levitation of the steel plate, a quadruple configuration of U-shaped electromagnets has been proposed. To resolve the issue of instability and attain more robust levitation, a centralized control algorithm based on a modified PID controller (I-PD) is designed for each degree of freedom by using the Manabe canonical polynomial technique. The model of the system is carried out using electromechanical energy conversion principles and verified by 3-D FEM analysis. An experimental bench is built up to test the system performance under trajectory tracking and external disturbance excitation. The results confirm the effectiveness of the proposed system and the control approach to obtain a full redundant levitation even in case of disturbances. The paper demonstrates the feasibility of the conveyance of steel plates by using the quadruple configuration of U-shaped electromagnets and shows the merits of I-PD controller both in stabilization and increased robust levitation.
Keywords: centralized control; control design; electromagnetic modeling; magnetic levitation; mechatronics; MAGNETIC-LEVITATION SYSTEM; SLIDING-MODE CONTROL; Computer Science; Engineering